Suicidal behavior and self-harm in girls with eating disorders - Koutek, Jiri; Kocourkova, Jana; Dudova, Iva (Neuropsychiatric disease and treatment, 2016)
Comorbid psychopathology, including self-harm and suicidal behavior, is often found in patients with eating disorders. To better understand the reasons for high comorbid psychopathology among eating disorders, self-harm, and suicidal behavior, we examined this comorbidity in female patients hospitalized with eating disorders. In a sample of 47 girls admitted for anorexia nervosa, atypical anorexia nervosa, and bulimia nervosa, 72% had depressive symptoms, 11% had obsessive-compulsive symptoms, 9% had anxiety disorder, 23% had substance abuse, and 57% had disharmonious personality development. Suicidal behavior was present in 60% of patients and self-harm in 49%. Association was found between self-harm and suicidality. In all, 68% of girls with eating disorders had a positive score in the Children's Depression Inventory questionnaire and 62% of them in the Child Adolescent Suicidal Potential Index questionnaire. Clinical examination of girls with eating disorders should focus on identifying the risk of suicidal behavior and self-harm.
Keywords: adolescent; self-harm; child; eating disorders; suicidal behavior